Analysis of stress responses in Astyanax larvae reveals heterogeneity among different populations. Issue 7 (6th August 2020) - Chin, Jacqueline S. R.; Loomis, Cody L.; Albert, Lydia T.; Medina‐Trenche, Shirley; Kowalko, Johanna; Keene, Alex C.; Duboué, Erik R.
Abstract: Stress responses are conserved physiological and behavioral outcomes as a result of facing potentially harmful stimuli, yet in pathological states, stress becomes debilitating. Stress responses vary considerably throughout the animal kingdom, but how these responses are shaped evolutionarily is unknown. The Mexican cavefish has emerged as a powerful system for examining genetic principles underlying behavioral evolution. Here, we demonstrate that cave Astyanax have reduced behavioral and physiological measures of stress when examined at larval stages. We also find increased expression of the glucocorticoid receptor, a repressible element of the neuroendocrine stress pathway. Additionally, we examine stress in three different cave populations, and find that some, but not all, show reduced stress measures. Together, these results reveal a mechanistic system by which cave‐dwelling fish reduced stress, presumably to compensate for a predator poor environment. Abstract : Following a stressor, surface Astyanax display prolonged freezing and elevated levels of the stress hormone cortisol. By contrast, cave dwelling Astyanax have little freezing, and their cortisol responses are significantly lower than surface fish. We also find that expression of the glucocorticoid receptor, a negative regulator of the neuroendocrine stress axis, is elevated in cave animals. Research Highlight: A. mexicanus cavefish larvae have reduced stress relative to surface conspecifics. The glucocorticoid receptor, a negative regulator of the stress axis, is upregulated in cavefish. Analysis of F2 fish reveal a distribution of stress behaviors